Socio-Economic Factors and Knowledge Influencing Newborn Care Practices: Experience at Dhaka Shishu Hospital - Begum, Housne Ara; Khan, Mohammad Faizul Haque (Ibrahim Medical College Journal, 2010)
Reducing maternal and neonatal mortality remains a big challenge for a developing country like Bangladesh. Mothers’ knowledge in neonatal care plays an important role in bringing down the mortality as well as morbidity. This study was conducted in Dhaka Shishu Hospital during the period of December 2007 to February 2008 and was based on primary data collected on socioeconomic status, knowledge and practice of mothers of neonates attending the hospital. A total of 400 mothers were interviewed. More than fifty percent mothers had an appropriate knowledge on feeding neonates, hand washing before handling neonates, care of eye, care of umbilicus and they were practicing as well. Where as less than fifty percent mothers had appropriate knowledge on keeping neonates warm, cutting hair, bathing, vaccination, oil massage and their practice rate also commensurate well with their knowledge level. Majority of the mothers were in the age group of 21-25 years, having completed primary education or passed SSC exam. They were house wives living in an urban area, with a monthly family income of 3000-7000 taka. Statistically significant association was found between socio demographic variables and knowledge and practices on neonatal care of the mothers. Ibrahim Med. Coll. J. 2010; 4(1): 17-20 Key words: Socio-economic factors; knowledge and practices; neonatal care DOI: 10.3329/imcj.v4i1.5930